1998
DOI: 10.1111/j.1600-0447.1998.tb10102.x
|View full text |Cite
|
Sign up to set email alerts
|

Hallucinatory modalities in prelingually deaf schizophrenic patients: a retrospective analysis of 67 cases

Abstract: In order to examine the effect of congenital or early acquired deafness on hallucinatory modalities in schizophrenia, we interviewed 67 prelingually deaf schizophrenic patients (using sign language) about their hallucinatory experiences over the entire course of their illness. We also analysed the clinical records of our subjects' previous hospitalizations. In our deaf sample, visual and tactile hallucinations were plainly over-represented as hallucinatory modalities in comparison with hearing schizophrenic sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…For instance, there is little research concerning the role of sensory deficits in the development of hallucinations and delusions in children and adolescents. This is in sharp contrast with studies with adult and old-age populations that suggest a role for sensory deficits in hallucinations and delusions [100][101][102][103][104][105][106][107][108][109][110][111]. Preliminary evidence suggests that this is also the case in younger agegroups [112], although more work is clearly needed.…”
Section: Discussioncontrasting
confidence: 75%
“…For instance, there is little research concerning the role of sensory deficits in the development of hallucinations and delusions in children and adolescents. This is in sharp contrast with studies with adult and old-age populations that suggest a role for sensory deficits in hallucinations and delusions [100][101][102][103][104][105][106][107][108][109][110][111]. Preliminary evidence suggests that this is also the case in younger agegroups [112], although more work is clearly needed.…”
Section: Discussioncontrasting
confidence: 75%
“…Authors continue to debate the existence of sound-based auditory hallucinations in deaf people. Past studies found self-reported rates of auditory hallucinations in deaf patients with schizophrenia to be comparable to rates reported in hearing patients (52%-59%) [9,10]. However, these findings have been examined more recently in light of deafness-related variables demonstrating that a deaf patient with schizophrenia's perceptual experience of "voice" hallucinations relates closely to the individual's language and past auditory experiences [12].…”
Section: Hallucinationsmentioning
confidence: 51%
“…The current consensus in the psychiatric literature is that similar to hearing patients, deaf patients with psychotic disorders experience hallucinations [9][10][11][12][13][14]. However, the manner in which hallucinations are manifested and experienced, particularly in prelingually deaf people (ie, deafness acquired prior to 3 years of age), remains unclear.…”
Section: Hallucinationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Currently, most research on the experience of hallucinations in D/deaf persons has concentrated on the form or sensory modality of these experiences (e.g. Atkinson et al , 2007; Schonaeur et al , 1998). This may be due to the obvious interest in the question about whether D/deaf people do actually “hear voices”.…”
Section: What Is Known About Hallucinations In D/deaf Persons?mentioning
confidence: 99%